(untitled) (Coordinates of Public Administration, 2026)
The article examines some features of language training of students in the context of the language situation in Ukrainian society, which is controlled by the state and with the involvement of the logical dimension. The genesis of the language situation in Ukraine, which is unique due to its bilingual nature, where Russian as the language of the empire for a long time dominated relations with Ukrainian, occupying leading positions in all spheres of life, and also influenced it, violating logic and structure. It is noted that the external aspect of the language conflict influenced the internal one, which was manifested in the contamination of the language with Russian-language calques. It was found that the long-standing interlingual conflict continued even after gained state independence, because the Ukrainian language was functionally weak compared to Russian, and only the state could resolve it at the legislative level. The role of the Law «On Ensuring the Functioning of the Ukrainian Language as the State Language» was analyzed, which established its dominance in all public spheres, and also obliged to adhere to the Spelling and replace Russian-language calques with specific Ukrainian counterparts. Some conflicts in the areas of anthroponymy (errors in surnames and names), toponymy (errors when renaming settlements) were considered, and the conclusion was made that the state should find means to unify the system of Ukrainian surnames in the direction of observing spelling norms. It is also necessary to unify the system of bibliographic descriptions, as well as compile online dictionaries of the Ukrainian language, where Russian-language calques should be eliminated as much as possible. It is noted that some frequent neologisms in modern language are copied from English without sufficient analysis, and therefore they also need to be replaced with specific equivalents, taking into account the exact semantics of the situation and the requirement of unambiguous terms in scientific language.